Free Space Optical Communications: An Overview - Sadiku, M. N. O.; Musa, S.M.; Nelatury, Sudarshan R. (European Scientific Journal, ESJ, 2016)
Bridging the so-called â€œlast mileâ€ in communication networks has revived keen interest in free-Space Optics (FSO), also known as fiber-free or fiberless optics, which is a technology that transports data via laser technology. It is a line-of-sight technology that currently enables optical transmission up to 2.5 Gbps of data, voice and video through the air at long distances (4km), allowing optical connectivity without deploying fiber-optic cable or securing spectrum licenses. It is moving closer to being a realistic alternative to laying fiber in access networks. This paper presents an introduction to FSO and the current state of its technology.